1992
DOI: 10.2172/7001745
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, health, and safety issues of sodium-sulfur batteries for electric and hybrid vehicles

Abstract: PrefaceThis report is the last of four volumes that identify and assess the environmental, health, and safety issues that may affect the commercial-scale use of sodium-sulfur (Na/S) battery technology as the energy source in electric and hybrid vehicles. The reports are intended to help the Electric and Hybrid Propulsion Division of the Office ofTransportation Technologies in the U.S. Department of Energy (D OFJEHP) determine the direction of its research, development, and demonstration (RD&D) program for Na/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Other in-vehicle safety issues are EV generic, and are not covered because they do not specifically apply to lithium SPE EV batteries. Previous analyses have discussed nonbattery-specific in-vehicle safety issues (Mark 1992).…”
Section: In-vehicle Safety Aspects Of Lithium Spe Batteriesmentioning
confidence: 99%
“…Other in-vehicle safety issues are EV generic, and are not covered because they do not specifically apply to lithium SPE EV batteries. Previous analyses have discussed nonbattery-specific in-vehicle safety issues (Mark 1992).…”
Section: In-vehicle Safety Aspects Of Lithium Spe Batteriesmentioning
confidence: 99%
“…. This analysis summarizes the discussion in a related report(Mark 1992) on the in-vehicle safety aspects of sodium-sulfur batteries for EVs where the issues are transferrable between the two different battery types. In addition, because there have bee n regulatory developments since the time the previous report was sent to press, this discussion updates some of the regulatory analysis provided in the earlier document.…”
mentioning
confidence: 90%
“…This section briefly reviews the safety concerns associated with EV use as identified by previous analyses and discusses the applicable regulations and standards. 1 In addition, the discussion presented here seeks to clarify issues that were previously identified as requiring further characterization (Mark 1992), such as TP-5475 crashworthiness and electrolyte spillage. While the primary focus of this report• is to assess the safety issues of EV s operating on Ni-MH batteries, most of the hazards described in this in-vehicle safety section are generic to EV s and can be thought of as applicable to a wide range of battery types and designs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation